Answer:
d = 1
Explanation:
Simplifying
d + -10 + -2d + 7 = 8 + d + -10 + -3d
Reorder the terms:
-10 + 7 + d + -2d = 8 + d + -10 + -3d
Combine like terms: -10 + 7 = -3
-3 + d + -2d = 8 + d + -10 + -3d
Combine like terms: d + -2d = -1d
-3 + -1d = 8 + d + -10 + -3d
Reorder the terms:
-3 + -1d = 8 + -10 + d + -3d
Combine like terms: 8 + -10 = -2
-3 + -1d = -2 + d + -3d
Combine like terms: d + -3d = -2d
-3 + -1d = -2 + -2d
Solving
-3 + -1d = -2 + -2d
Solving for variable 'd'.
Move all terms containing d to the left, all other terms to the right.
Add '2d' to each side of the equation.
-3 + -1d + 2d = -2 + -2d + 2d
Combine like terms: -1d + 2d = 1d
-3 + 1d = -2 + -2d + 2d
Combine like terms: -2d + 2d = 0
-3 + 1d = -2 + 0
-3 + 1d = -2
Add '3' to each side of the equation.
-3 + 3 + 1d = -2 + 3
Combine like terms: -3 + 3 = 0
0 + 1d = -2 + 3
1d = -2 + 3
Combine like terms: -2 + 3 = 1
1d = 1
Divide each side by '1'.
d = 1
Simplifying
d = 1